The development of a model of behaviour analysis in a residential service for children with autism - Lindsay Barrie; Vivienne Richardson (Scottish Journal of Residential Child Care)
Taylaughlan House is a Fife Council social work residential resource and it currently provides full-time placements for three children who have a diagnosis of autism and display extremely challenging behaviour. Two of these children attend full-time education at a local special needs school. Taylaughlan House consists of two adjoining houses.